Awe promotes moral expansiveness via the small-self - Song, Ji Young; Klebl, Christoph; Bastian, Brock (Frontiers in Psychology, 2023)
The experience of awe has been shown to challenge how people think about themselves and the world around them, linking them to something greater than themselves. We investigated whether this emotional experience of awe may also challenge the boundaries of our moral consideration, leading to a generalised expansion in our moral worlds. Across five studies (N = 990), we examined whether awe might promote moral expansiveness; that is, increased moral concern across a broad range of entities (e.g., out-groups, animals, plants, environments). Cross-sectional Studies 1a & 1b, found dispositional awe was related to greater moral expansiveness. Experimental Studies 2 and 3, using video-induced awe, found consistent indirect effects on moral expansiveness, via self-reported awe and the small-self sense of vastness. Experimental Study 4, using Virtual Reality induced awe, found those in the awe condition (vs. control) reported greater moral expansiveness, and this was fully mediated by the small-self sense of vastness. Our findings show awe expands our sense of connectedness to the broader world, and through this, increases the breath of our moral concern.